Mobility Management in LTE Heterogeneous Networks - Karandikar, Abhay; Akhtar, Nadeem; Mehta, Mahima; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2017)
This book is the first of its kind, compiling information on the Long-Term Evolution (LTE) standards, which are enhanced to address new mobility-related challenges in Heterogeneous Networks (HetNets). It identifies the related challenges and discusses solutions and the simulation methodology for modeling HetNet mobility - cutting-edge information that was previously accessible only in the form of 3GPP specifications and documents, and research papers. The book reviews the current LTE mobility framework and discusses some of the changes for enhancing mobility management in HetNets. It describes the measurement procedures, handover (HO) mechanisms and HO success/failure scenarios. HetNets are intended to provide very high spectral eﬃciency while ensuring seamless coverage by deploying low-power nodes within the umbrella macrocell network. While mobility management in homogeneous networks is well understood, LTE standards are being enhanced to address the HetNet-specific mobility management challenges emerging. The book addresses these aspects in a succinct and understandable form, offering a valuable resource for researchers and professionals working in the area of HetNet mobility and a ready reference guide for practicing engineers and researchers.
Chapter 1: Introduction -- Chapter 2: Mobility Management in LTE Networks -- Chapter 3: Methodology for 3GPP Modeling -- Chapter 4: Mobility Challenges in LTE Heterogneous Networks -- Chapter 5: Enhancements for Mobility State Estimation in LTE HetNet -- Chapter 6: Optimization of Mobility-related Parameters.
Keywords: Telecommunication; Computer networks .; Communications Engineering, Networks; Computer Communication Networks